Managerial accounting for dummies - Holtzman, Mark P. (--For dummies., 2013)
The easy way to master a managerial accounting course Are you enrolled in a managerial accounting class and finding yourself struggling? Fear not! Managerial Accounting For Dummies is the go-to study guide to help you easily master the concepts of this challenging course. You'll discover the basic concepts, terminology, and methods to identify, measure, analyze, interpret, and communicate information in the pursuit of an organization's goals. Tracking to a typical managerial accounting course and packed with easy-to-understand explanations and real-life examples.